2021
DOI: 10.26451/abc.08.01.01.2021
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Animal Welfare at the Zoo: The Impact of an Animal Visitor Interaction Program on Chickens

Abstract: Many modern zoos strive to create connections between guests and animals through animal visitor interaction (AVI) programs. However, there has been relatively little research into the effect of AVI programs on the welfare of program animals. Previous research has revealed three factors that may affect AVI program animal welfare: species differences, handling and transport, and the provision of choice and control. We assessed the effects of an AVI program designed with these factors in mind on the behavior of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Previous research has found that goats, in comparison to other domestic species, may be less influenced by the presence of unfamiliar people (Anderson et al, 2004;Farrand et al, 2014), especially when options to move away from people are provided (Anderson et al, 2002). Considering how animals use their space is a simple but effective way to infer their comfort in the presence of visitors, as animals will generally tend to avoid situations that make them less comfortable if possible (Learmonth et al, 2018;Ramont et al, 2021;Saiyed et al, 2019;Wark et al, 2019). Our results suggest that goats are not averse to the presence of unfamiliar people, and that they may be attracted to them under certain conditions, namely, with the option to retreat and a limit on the maximum number of people present.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has found that goats, in comparison to other domestic species, may be less influenced by the presence of unfamiliar people (Anderson et al, 2004;Farrand et al, 2014), especially when options to move away from people are provided (Anderson et al, 2002). Considering how animals use their space is a simple but effective way to infer their comfort in the presence of visitors, as animals will generally tend to avoid situations that make them less comfortable if possible (Learmonth et al, 2018;Ramont et al, 2021;Saiyed et al, 2019;Wark et al, 2019). Our results suggest that goats are not averse to the presence of unfamiliar people, and that they may be attracted to them under certain conditions, namely, with the option to retreat and a limit on the maximum number of people present.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in a recent study investigating guinea pig responses to zoo visitors, Powell et al (2020) found that domesticated guinea pigs housed in an exhibit allowing them to be touched by visitors showed no systematic changes in glucocorticoids or body weight indicative of welfare compromise relative to when they were housed off exhibit without visitors touching them. Both Ramont et al (2021) and Powell et al (2020) interpret their zoo-based findings in light of research demonstrating that reduced behavioral and physiological responsiveness to potentially stressful stimuli, including human presence, is a common feature of domestication (e.g., Fallahsharoudi et al, 2015;Fraser & Broom, 1990;Künzl & Sachser, 1999;Price, 1984).…”
Section: _____________________________________________________________________________________mentioning
confidence: 99%
See 1 more Smart Citation
“…In many contexts, captive animals have been domesticated, e.g., on farms, pets, and thus, adapted to the presence of humans. For example, domestic chickens show little behavioral responses to visitors in an interaction program (Ramont et al, 2021). Typical zoo animals, born in captivity over generations, might have undergone a certain selection for tolerance towards humans (Frankham et al, 1986;McDougall et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The present study contributes novel insights into behavioral responses of non-domesticated avian species to the presence of zoo visitors. Most previous studies on visitors' effects have been conducted on mammals and studies on birds are rare (de Azevedo & Lima, 2012;Ramont et al, 2021;. In order to better understand the effects of zoo visitors on avian welfare, more studies on bird species are necessary.…”
Section: Discussionmentioning
confidence: 99%